Methods of test for orthoboric acid (boric acid), diboron trioxide (boric oxide), disodium tetraborates, sodium perborates and crude sodium borates for industrial use. Determination of matter insoluble in alkaline medium and preparation of test solutions of crude sodium borates Part 10, (28th February 1979) - British Standards Institution,
No abstract available